2016
DOI: 10.18632/oncotarget.7624
|View full text |Cite
|
Sign up to set email alerts
|

Butein inhibits cell proliferation and induces cell cycle arrest in acute lymphoblastic leukemia via FOXO3a/p27kip1 pathway

Abstract: Acute lymphoblastic leukemia (ALL) is a common hematological malignancy characterized by the uncontrolled proliferation of leukemia cells in children. Discovering and developing effective chemotherapeutic drugs are needed for ALL. In this study, we investigated the anti-leukemic activity of butein and its action mechanisms in ALL. Butein was found to significantly suppress the cellular proliferation of ALL cell lines and primary ALL blasts in a dose-dependent manner. It also induced cell cycle arrest by decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…Apoptosis induction is an important biological effect after butein treatment and different molecular mechanisms including PI3K/Akt/mTOR pathway inhibition 22 , suppression of STAT3 activation 47 , reactive oxygen species generation 48 , inhibition of cyclooxygenase-2 expression 49 were reported to be engaged in the apoptosis induction by butein. Consistent with the concentrations used in other studies 23 , 24 , 50 , in our study, at the concentration rang of 10-60μM, butein dose-dependently inhibited HCC cell proliferation, colony formation and induced G2/M cell cycle arrest and apoptosis. Differently, for the first time, we clarified that Aurora B was a potential target of butein in HCC.…”
Section: Discussionsupporting
confidence: 92%
“…Apoptosis induction is an important biological effect after butein treatment and different molecular mechanisms including PI3K/Akt/mTOR pathway inhibition 22 , suppression of STAT3 activation 47 , reactive oxygen species generation 48 , inhibition of cyclooxygenase-2 expression 49 were reported to be engaged in the apoptosis induction by butein. Consistent with the concentrations used in other studies 23 , 24 , 50 , in our study, at the concentration rang of 10-60μM, butein dose-dependently inhibited HCC cell proliferation, colony formation and induced G2/M cell cycle arrest and apoptosis. Differently, for the first time, we clarified that Aurora B was a potential target of butein in HCC.…”
Section: Discussionsupporting
confidence: 92%
“…Foxo3a plays a vital role in gene regulation in tumorigenesis. Resent research report that as transcription factor, Foxo3a inhibited proliferation and induced cell cycle arrest by controlling cyclin-dependent kinase inhibitor p27kip1 [39], contributing to cancer cell apoptosis by regulation of proapoptotic member [40]. Previous reports have showed Foxo3a were overexpressed in less aggressive types of GC [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the preceding reports have also suggested the same activities against different cancer cells such as breast, blood, liver, cervical etc. (Yang et al, 2012;Liao et al, 2018;Tang et al, 2016;Yang et al, 2018). For instance, Yang et al, (2018) reported that butein reduced the viability of cervical cancer cells through a proapoptotic effect by blocking inhibitor of apoptosis (IAP) proteins and activating extrinsic as well as intrinsic proapoptotic cascades.…”
Section: Discussionmentioning
confidence: 99%